(Sobre)vivências: um estudo fenomenológico-existencial acerca dos modos de ser sendo crianças e adolescentes em situação de rua - Paiva, Jacyara Silva de (2006)
The phenomenon of children and adolescents experiencing destitution and abandonment has become even worse in our country. This felt fact instigates us to take a position and to research this matter in hand which urgently unveils itself in our society. This study aims to answer three questions: 1) How have I, as a researcher, become interested in streets and how have streets become my place of work, evoking a feeling into my ways of being as a(n) (social) educator conducting a research in streets?; 2) What is and How is to exist in streets undergoing such a status quo?; 3) How can we understand the power of a group in the existential survival of children and adolescents living in streets? Thus, the subject or matter/phenomenon of this study/research is the genesis (what is) and the interdynamics not separate from the genesis (how is) of the human being (boy or girl and/or child or adolescent living in streets) in the ways (s)he reveals her/himself, shows her/himself, appears, and allows her/himself to be captured by the look of a scientist who also has a feeling relation to the streets. To do so, we have resorted to the the exitential-phenomenological inspiration, since we are interested in what has been lived and exprerienced by these human beings. The chosen theoretical marks have risen out of the categories of: Paulo Freire (the importance of dialogue ), Victor E. Frankl ( life sense ), and Hiran Pinel ( the ways of being as being oneself in the world s everyday life ). We understand that children and adolescents show diverse ways of being as being ... ephemeral, finite, incomplete, etc. like life itself. Therefore, sometimes they are bold , sometimes they are dramatic in their modes of lives; however, always being brave and having ingenious tactics such as forming survival and resistance groups in order to be able to live in streets or discussing their matters so as to understand themselves, even if they do not manage to meet regularly. This study has shown significant implications to the construction of public politics (social and educational) and politics of impact to the social educator s everyday live and to that of the school teacher s as well. Such inclusive processes can be made viable since these ways of being as being a(n) are understood.